A produção de pesquisa em educação e as políticas públicas no DF (2006-2012): uma articulação necessária - Chaves, Clara de Souza (2014)
This work falls within the field of study of the research line of public policies managment and economy of education from Universidade Católica de Brasília (UCB) (Catolic Brasílias’s University). The goal of the study was the academic production from the employees of Education Department of the State of Distrito Federal (SEDF) removed as researchers to make studies in the scope of the career planning of the mastership of Distrito Federal, started in 2005 with the Law # 3621 of July 14th of 2005. The study was focused on Academic production of pos graduated programs strictly speaking (stricto sensu) in Education developed on seach lines that involves policy, managment and economy of education from Catolic University of Brasília and public policies and education managment of Brasilia’s University. (UNB). Between 2006 and 2012 turned to basic education. The methodology adopted on the study was: the qualitative search of exploratory character, when deal with data source. It was used three qualitative search methods: Bibliographic search, document analysis, and interview. The dissertation was splited in 5 chapters. The first charpter deal with education as a inalienable right and requirement as a practice to citizenship development. The second charpter presentes a bibliography review about education researching developed on Brasil. The third charpter show us the portrait of the pos graduated in Brasil and Distrito Federal (Capital). The fourfh charpter show the public education on Distrito Federal the structure and career profile of mastership. The charpter five presentes the feedback of documentary search maded by library system of UNB and UCB on the Educationemployess improvment school on Distrito Federal and the interviews maked. The results of the search demonstrate a convergence between the seachers view point, universities and public institutions when you talk about to stablish a conection between academic production and the problems and challengers of public education on Distrito Federal.